Qualificar a cidade para o pedestre - um tema histórico e um desafio atual para o município (São Paulo) - Katia Canova (Confins)
Urban studies have always been more guided by economic modes and their techniques of production than the forms of appropriation by the citizens who live or enjoy it. It was only in the 1960s that authors such as Henri Lefebvre, Milton Santos and Jane Jacobs began to come up with a new discussion on urban space: the importance of the user's eyesight and perception, the human scale, public spaces, diversity, the value of connectivity / accessibility and the vital need for the practice of reuse and preservation of the built heritage and memory of places. In addition to these are Mark Girouard and Fraya Frehse with a more historical and social investigation of urban dynamics, Jan Gehl and Janette Sadik-Kahn with practical applications and rapid transformations of public spaces, transforming areas underutilized by the 1950s roadside practice in places to live, to contemplate, finally of enjoyment for the people who live the experience of pedestrian and cyclist in great world-wide cities. This paper intends to explore these public spaces, streets and corners, by historical cartography, photos and social studies with pedestrian as a focus. The goal is the mapping of historical scenes explored by Frehse beyond the bars and bakeries that remained through the years until today as the urban sociability resistance parts. Also brings the discussion of numerical and cartographic indicators to support urban planning decisions, as well as the diversification of discussion groups and the application of new solutions for the appropriation of urban public places.